Les recherches en communication organisationnelle en France : quelques éléments de bilans et de perspectives - Christian Le Moënne; Sidonie Gallot (Communiquer)
This contribution, in the form of an interview, deals with deployment processes, developments and prospects of research in organizational communication in France. In light of their contextual characteristics, we try to show their evolution through the point of view of Christian Le Moënne, who was responsible for the creation of the French research group in organizational communications Org&Co. This interview do not intend to restore the “History”, or to draw up a comprehensive overview of the work done – which, given their diversity, would involve major bias –, and it does not seek to establish a linear comparison with international research. In contrast, it offers a vision fed on research in organizational communication in France through the terms of their development, the effects of contexts, their links with the sciences of information and communication. It proposes a reflexion on logics of institutionalization and legitimization of research fields and programs, on scientific and professional acceptability degrees, etc., on a plurality of phenomena which are involved and participate in construction and definition of a research program as large and complex that are organizational communications.